(untitled) (Biological Sciences - PJSIR, 2016)
Enhancement of the amylase productivity by Aspergillus flavus was investigated. Spores of strain were exposed to ultraviolet (UVC) radiation and 10 different mutants were selected and isolated from starch plate agar on the basis of the visible clearance zone around the colonies. The amylase production by selected mutants was evaluated under solid state fermentation. One mutant of A. flavus FSS63UV8 showed higher biosynthesis level of amylase (733 IU/g), which was 3.35 fold higher than that detected in the parental strain. Physical parameters optimisation revealed that the optimum pH and temperature for amylase production obtained by mutant are 7.0 and 35°C, respectively. Among several tested agricultural wastes , wheat bran was found to support the highest yield of amylase after 5 days of incubation. A. flavus FSS63UV8 strain proved to be a promising microorganism for a high amylase production in a simple medium.